Handbook of Paediatric Problems - Basnet, Sudha (Journal of Nepal Paediatric Society, 2009)
Professor Pushpa Raj Sharma "Handbook of Paediatric Problems" Third Edition Makalu Publication House, Dilli Bazar, Kathmandu, Nepal 2009 724 pp Price: Rs. 500/- (ISBN 978-9937-503- 21-1) DOI: 10.3126/jnps.v30i1.2466 Journal of Nepal Paediatric Society Vol.30(1) 2010 69